2011
DOI: 10.1073/pnas.1013846108
|View full text |Cite
|
Sign up to set email alerts
|

Host plant shifts affect a major defense enzyme inChrysomela lapponica

Abstract: Chrysomelid leaf beetles use chemical defenses to overcome predatory attack and microbial infestation. Larvae of Chrysomela lapponica that feed on willow sequester plant-derived salicin and other leaf alcohol glucosides, which are modified in their defensive glands to bioactive compounds. Salicin is converted into salicylaldehyde by a consecutive action of a β-glucosidase and salicyl alcohol oxidase (SAO). The other leaf alcohol glucosides are not oxidized, but are deglucosylated and esterified with isobutyric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 47 publications
2
31
0
Order By: Relevance
“…However, among the predicted enzymes in the Chrysomelina secretions, only the functionally characterized salicyl alcohol oxidases (SAOs) from salicin-sequestering species have been analysed with respect to their ancestry [16,20,21]. These SAOs belong to the glucose-methanol-choline (GMC) oxidoreductase multi-gene family [22,23] and convert salicyl alcohol into salicylaldehyde [20].…”
Section: Introductionmentioning
confidence: 99%
“…However, among the predicted enzymes in the Chrysomelina secretions, only the functionally characterized salicyl alcohol oxidases (SAOs) from salicin-sequestering species have been analysed with respect to their ancestry [16,20,21]. These SAOs belong to the glucose-methanol-choline (GMC) oxidoreductase multi-gene family [22,23] and convert salicyl alcohol into salicylaldehyde [20].…”
Section: Introductionmentioning
confidence: 99%
“…Targeting the defensive glands of juvenile poplar leaf beetles by RNA interference Recently, a 1872-bp CpopSAO cDNA (Genbank/ HQ245154.1) encoding a 69 kDa protein for conversion of 2 into 3 was identified from the larval defensive glands of C. populi [13,14] (figure 2a). It belongs to the glucose -methanol -choline (GMC) family of oxidoreductases [38].…”
Section: Results (A)mentioning
confidence: 99%
“…This shows a distinct function of this enzyme in vivo. Before, Kirsch et al [13] showed activity only in in vitro assays. Evidently, RNAi is a valuable technique for identifying in vivo relevance for unknown proteins in defensive glands.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations